1981
DOI: 10.1159/000194356
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blocker Therapy with Metoprolol in the Hyperventilation Syndrome

Abstract: 16 patients suffering from a hyperventilation syndrome were treated with metoprolol 2dd 100 mg and an identical placebo in a double-blind, cross-over trial. Before therapy and after metoprolol and placebo therapy a ventilatory response to CO2 was taken, VC and FEV1 a hyperventilation provocation test, blood gas values, and the subjective experiences of the patients were documented. The ventilatory response to CO2 was described in terms of decrease or increase of ventilation: be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Fur thermore, this study shows that the effects persist longer than the 4-week period we used in our previous study [Folgering and Cox, 1981]. The /Fblocker is at least as ef fective as other kinds of therapy or place bo in this respect.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Fur thermore, this study shows that the effects persist longer than the 4-week period we used in our previous study [Folgering and Cox, 1981]. The /Fblocker is at least as ef fective as other kinds of therapy or place bo in this respect.…”
Section: Discussionsupporting
confidence: 47%
“…In a double-blind cross-over study we treated this group of hyperventilation patients with metoprolol (2x 100 mg dd) during 4 weeks and found a significant de pression of ventilation and consequently an increase in Pa.co:-The subjective com plaints of the patients were assessed semiquantitatively: more complaints, less com plaints or no change. No clear-cut effect on the subjective feeling of well-being was found in that investigation [Folgering and Cox, 1981]. Everyday practice deviates considerably from a carefully planned prospective double-blind cross-over study.…”
mentioning
confidence: 57%
“…The latter structure may be involved in emotional disorders and be under the influence of the " mental state" which has an important bearing on both breathing be haviour and the VOR. Folgering and Cox (1981) have shown that noradrenaline excretion is significantly in creased in patients with the HVS. This would fit into a stress model in which both VH and the HVS can occur concomitantly.…”
Section: Vh the Hvs And Whiplash Injurymentioning
confidence: 98%
“…More recently, a sympathetic rest ing tone was shown in the carotid body of the cat [ 16], Fitzgerald et al [ 12] states 'that any physiological condition that increases sympathetic activity and catecholamine release could be expected to stimulate re spiration by stimulating the peripheral chemoreflex'. We suggest this might also be true for anxiety [15,38] or for the sub ject's mental state evoked by experimental conditions [18,24], which have been shown to alter the breathing pattern [2].…”
Section: Discussionmentioning
confidence: 87%